Quest of ancient fire: Mahakavi’s Shakuntala and the contemporary Nepalese society - Adhikari, Tara Prasad (Journal of Nepalese Studies, 2024)
’Quest of Ancient Fire: Mahakavi’s Shakuntala and the Contemporary Nepalese Society’ penetrates the question of the relevancy of ancient myths in new contexts. Using Mahakavi Laxmi Prasad Devkota’s Shakuntala as the primary text, for it is textual criticism, this study looks into Devkota’s rewriting of the Shakuntala myth, assessing its implications for contemporary Nepalese society. By scrutinizing Mahakavi Devkota’s portrayal of ancient Hindu society, its people, gender dynamics, and the nexus between past and present, this Exploration seeks the multifaceted relationship between literature, history, and society. Its major findings emphasize that Devkota could connect the past with the present as his writings are relevant in the modern context as well. Furthermore, this study reads the implications of Devkota’s mythical adaptations as a request for cultural consolidation. Employing the New Historicist perspective, the study investigates how Devkota highlights historical themes and encourages readers to reexamine the deeper nuances of Nepalese culture and history. Eventually, this research illustrates how Devkota’s legacy is still indispensable in the Nepalese context.